Determination and Purification of Ricin Protein from Ricinus communis L. Seeds using CLC (Column Liquid Chramotagoraphy) and FPLC (Fast Protein Liquid Chramatography) - Irma Erika Herawati; Ronny Lesmana; Jutti Levita; Anas Subarnas (Indonesian Journal of Pharmaceutical Science and Technology, 2021)
Proteins found in all biological systems, from prokaryotes to eukaryotes. Ricin, one of the most toxic substances known isolated from Ricinus communis L. seeds, is a heterodimeric two-domain polypeptide protein that includes chain A (30 kDa) and chain B (35 kDa) linked by a disulfide bond. Ricin binds to cells by the B chain and is then internalized. Ricin has been reported as a potential chemical for cancer treatment. The measurement of protein concentration in an aqueous sample is an important assay in biochemistry research. However, so far, the quantification of ricin protein is not much reported. In this study, the quantification ricin protein extracted from R. communis L. seeds originated from Nganjuk, East Java, Indonesia. The techniques used column liquid chromatography (CLC) and fast protein liquid chromatography (FPLC), followed by quantification protein content used Bradford method. Results showed that all techniques positively confirm the presence of ricin protein. Ricin protein content were 0.171±0.021 mg/mL and 0.382±0.023 mg/mL using CLC and FPLC respectively. This study might contribute to understanding the biological and chemical properties of the ricin protein of R. communis L. seeds. Ricin protein content measured with FPLC were higher than CLC. Keywords: Ricin, Ricinus communis,CLC, FPLC.